How Do the Poor Get the Justice They Deserve? Study of the Legal Aid Law in Indonesia - Muhammad Irfan Faza (Universitas Negeri Semarang, 2021)
Indonesia is a country that respects and upholds human rights. All Indonesian people have the same rights when confronted with the law. They have the same position and should not be discriminated against. economically disadvantaged people find it difficult to obtain a legal position. To examine this problem, the authors use the approach used is an approach using legal science and social science called the socio-legal approach. The poor who are experiencing legal problems has the right to get the same treatment as others. They are entitled to get assistance from advocates. The guarantee of the community to achieve justice can be interpreted as equal rights to obtain, use and benefit from the judicial process obtained through the courts or through informal mechanisms. Providing legal assistance to the poor does not always run smoothly, there must be obstacles that prevent it. However, despite experiencing obstacles in providing legal aid in Indonesia, it can already be said to be effective, proven by the many legal cases that use legal assistance without the need for the poor to pay.